A review of food-grade vectors in lactic acid bacteria: from the laboratory to their application. (3rd April 2017) - Landete, José Maria
Abstract: Lactic acid bacteria (LAB) have a long history of use in fermented foods and as probiotics. Genetic manipulation of these microorganisms has great potential for new applications in food safety, as well as in the development of improved food products and in health. While genetic engineering of LAB could have a major positive impact on the food and pharmaceutical industries, progress could be prevented by legal issues related to the controversy surrounding this technology. The safe use of genetically modified LAB requires the development of food-grade cloning systems containing only the DNA from homologous hosts or generally considered as safe organisms, and not dependent antibiotic markers. The rationale for the development of cloning vectors derived from cryptic LAB plasmids is the need for new genetic engineering tools, therefore a vision from cryptic plasmids to applications in food-grade vectors for LAB plasmids is shown in this review. Replicative and integrative vectors for the construction of food-grade vectors, and the relationship between resistance mechanism and expression systems, will be treated in depth in this paper. Finally, we will discuss the limited use of these vectors, and the problems arising from their use.